Lithium iron phosphate positive electrode material, preparation method thereof and application of semi-solid battery

CN122552507BActive Publication Date: 2026-10-09SHANDONG SACRED SUN POWER SOURCES
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
CN202611050020.9
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2026-07-15
Publication Date
2026-10-09
Estimated Expiration
2046-07-15

AI Technical Summary

Technical Problem

然而,目前磷酸铁锂体系在半固态电池中的应用存在以下问题:磷酸铁锂的橄榄石结构决定其本征缺陷,存在低电子电导率和较慢的锂离子扩散速率,而在半固态电池中,固态电解质的使用进一步限制了离子的传输路径,使得锂离子在正极材料内部的扩散更加困难,导致电池在高倍率充放电时性能不佳;而且磷酸铁锂正极材料与固态电解质之间界面性能阻碍锂离子在界面处的传输,增加电池电阻,降低电池能量效率和充放电性能

Benefits of technology

1、本申请中首先将磷酸铁锂核体进行中间层包覆,形成硅酸盐包覆层,硅酸盐包覆层一方面可以防止磷酸铁锂与固态电解质直接接触,抑制界面副反应,同时还可以缓解充放电过程中磷酸铁锂的体积变化,有效抑制磷酸铁锂在充放电过程中结构变化,提高正极材料的循环稳定性,而中间包覆层中介孔模板剂的添加在水热反应中引导形成规整的介孔结构,然后热解煅烧去除模板剂后形成介孔结构,增加材料比表面积,为锂离子提供更多的扩散路径,缩短传输距离,而且介孔结构还降低界面离子传输阻力;

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
  • Figure SMS_2
    Figure SMS_2
Patent Text Reader

Abstract

The application relates to the field of lithium battery materials, and specifically discloses a lithium iron phosphate positive electrode material, a preparation method thereof and a semi-solid battery applying the lithium iron phosphate positive electrode material. The preparation method comprises the following steps: S1, dispersing a lithium iron phosphate core in a mixed aqueous solution containing LiNO3, (NH4)3PO4 and Na2SiO3, reacting, adding a mesoporous template agent, centrifuging, washing, drying, calcining and preparing coated lithium iron phosphate; S2, mixing the coated lithium iron phosphate, porous carbon powder and nitrogen-containing phenolic resin prepolymer with ethanol to form a suspension, performing spray drying and preparing composite precursor particles; S3, pyrolyzing the composite precursor particles to prepare the lithium iron phosphate positive electrode material; and the application further discloses the lithium iron phosphate positive electrode material prepared by the above preparation method and a semi-solid battery applying the lithium iron phosphate positive electrode material. The application has the characteristics of improving lithium ion transmission performance of the lithium iron phosphate positive electrode material and further improving the rate performance and cycle stability of the battery.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This application relates to the field of battery materials, and more specifically, to a lithium iron phosphate cathode material, its preparation method, and its application in a semi-solid-state battery. Background Technology

[0002] With increasing global emphasis on environmental protection and sustainable development, fields such as new energy vehicles and energy storage systems have experienced rapid growth, leading to increasingly higher performance requirements for batteries. Traditional lithium-ion batteries mostly use liquid electrolytes; however, liquid electrolytes pose safety hazards such as leakage and flammability / explosion, and also face certain bottlenecks in improving energy density.

[0003] Semi-solid-state batteries combine some features of liquid and all-solid-state batteries. While retaining a certain amount of liquid electrolyte, they introduce a solid electrolyte, significantly reducing the liquid electrolyte content to only a small amount to ensure rapid lithium-ion movement and thus fast charging. Simultaneously, the introduction of solid materials significantly improves safety and effectively suppresses lithium dendrite growth, which can lead to short circuits. It is currently the only technology to achieve high energy density in mass-produced vehicles.

[0004] Lithium iron phosphate (LiFePO4), as an important cathode material, has been widely used in the field of lithium-ion batteries due to its advantages such as wide availability of raw materials, low price, long cycle life, high safety, and environmental friendliness. However, the application of lithium iron phosphate in semi-solid-state batteries currently faces the following problems: The olivine structure of lithium iron phosphate inherently results in low electronic conductivity and a slow lithium-ion diffusion rate. In semi-solid-state batteries, the use of solid electrolytes further restricts the ion transport path, making lithium-ion diffusion within the cathode material more difficult, leading to poor battery performance at high charge-discharge rates. Moreover, the interfacial properties between the lithium iron phosphate cathode material and the solid electrolyte hinder lithium-ion transport at the interface, increasing battery resistance and reducing battery energy efficiency and charge-discharge performance.

[0005] To address the aforementioned issues, further research and development of lithium iron phosphate-based cathode materials is needed to solve these problems and produce high-performance lithium iron phosphate cathode materials, which is of great significance for the development and widespread application of semi-solid-state batteries. Summary of the Invention

[0006] To improve the lithium-ion transport performance of lithium iron phosphate cathode materials and further enhance the rate performance and cycle stability of batteries, this application provides a semi-solid-state battery containing lithium iron phosphate cathode material, its preparation method, and its application.

[0007] In a first aspect, this application provides a method for preparing a lithium iron phosphate cathode material, employing the following technical solution: A method for preparing a lithium iron phosphate cathode material includes the following steps: S1. The lithium iron phosphate core is dispersed in a mixed aqueous solution containing LiNO3, (NH4)3PO4 and Na2SiO3, and a hydrothermal reaction is carried out under alkaline conditions. At the same time, a mesoporous template agent is added. After the reaction is completed, the core is centrifuged, washed, dried, and then calcined under an inert atmosphere to remove the mesoporous template agent, thus obtaining coated lithium iron phosphate. S2. The prepolymer of coated lithium iron phosphate, porous carbon powder and nitrogen-containing phenolic resin obtained in step S1 is mixed with ethanol, ultrasonically dispersed to form a suspension, and then spray-dried to obtain composite precursor particles. S3. Lithium iron phosphate cathode material is prepared by pyrolyzing composite precursor particles in a nitrogen atmosphere.

[0008] By adopting the above technical solution, this application first coats the lithium iron phosphate core with an intermediate layer to form a silicate coating layer. The silicate coating layer can prevent lithium iron phosphate from directly contacting the solid electrolyte, suppressing interfacial side reactions, and also alleviate the volume change of lithium iron phosphate during charging and discharging, effectively suppressing the structural changes of lithium iron phosphate during charging and discharging, and improving the cycle stability of the cathode material. The addition of a mesoporous template agent in the intermediate coating layer guides the formation of a regular mesoporous structure in the hydrothermal reaction. After the template agent is removed by pyrolysis and calcination, a mesoporous structure is formed, which increases the specific surface area of ​​the material, provides more diffusion paths for lithium ions, shortens the transport distance, and also reduces the interfacial ion transport resistance.

[0009] Then, it is mixed with porous carbon powder, nitrogen-containing phenolic resin prepolymer, and ethanol for post-treatment. A conductive network is constructed using the porous carbon powder. The high conductivity of the porous carbon powder compensates for the inherently low electronic conductivity of lithium iron phosphate. Furthermore, the pore structure of the porous carbon powder complements the mesopores of the lithium iron phosphate coating layer, forming a three-dimensional conductive network that promotes rapid electron transport within the cathode material. Its pore structure provides additional diffusion paths for lithium ions, solving the problem of ion transport obstruction caused by traditional dense carbon layers. In addition, the nitrogen-containing phenolic resin prepolymer carbonizes during pyrolysis, further enhancing the continuity of the conductive network and improving high-rate charge / discharge performance. The nitrogen-containing phenolic resin prepolymer is transformed into a nitrogen-containing carbon layer. Nitrogen doping further improves the electronic conductivity and surface wettability of the carbon material, enhancing interfacial compatibility with the solid electrolyte. Its surface nitrogen-containing functional groups form lithium-ion transport bridges with lithium ions, not only reducing interfacial impedance but also increasing the migration rate of lithium ions at the interface. Ultimately, nitrogen doping improves electronic conductivity and the lithium-ion diffusion system, reduces interface impedance, and thus improves rate performance and cycle stability.

[0010] Optionally, the mesoporous template agent in step S1 may be polymethyl methacrylate microspheres or PEO-PPO-PEO block copolymers.

[0011] Optionally, in step S1, LiNO3, (NH4)3PO4 and Na2SiO3 are added in a molar ratio of Li:P:Si of 1:(0.8-1):(0.05-0.1), and the concentration of LiNO3 in the mixed aqueous solution is 0.1-0.5 mol / L, and the mass ratio of lithium iron phosphate core to mixed aqueous solution is 1:(4-5). The alkaline conditions are pH 9-10, and the hydrothermal reaction is carried out at 60-80℃. The amount of mesoporous template agent added is 3-6 wt% of the mass of lithium iron phosphate core. The calcination temperature is 350-450℃, and the calcination time is 2-3 hours.

[0012] By adopting the above technical solution, the above calcination treatment removes the mesoporous template agent to form a porous coating layer, thereby increasing the lithium-ion diffusion channels.

[0013] Optionally, the nitrogen-containing phenolic resin prepolymer in step S2 is prepared by the following steps: Phenol was heated to 50-55℃ in an oil bath, and the pH was adjusted to 8-9. Formaldehyde solution and urea were added under stirring, and the temperature was raised to 80-85℃. The reaction was maintained at this temperature for 2-3 hours. After cooling, water was added to dilute the solution and the pH was adjusted to 6-7. The mixture was allowed to stand and separate into layers. The lower layer was taken and dehydrated until the solid content was 40-50%, thus obtaining a nitrogen-containing phenolic resin prepolymer.

[0014] By adopting the above technical solution, this application uses phenol and formaldehyde as raw materials to prepare phenolic resin. Phenol reacts with formaldehyde under alkaline conditions to form hydroxymethylphenol intermediate. Urea is added as a nitrogen source and reacts with formaldehyde to generate hydroxymethylurea, which further condenses with phenol. The condensation of hydroxymethylphenol and hydroxymethylurea forms a nitrogen-containing phenolic resin network structure. The nitrogen-containing phenolic resin prepolymer decomposes into carbon in the pyrolysis step to form a conductive carbon network, which encapsulates lithium iron phosphate, improving electronic conductivity. Combined with porous carbon powder, a three-dimensional conductive network is constructed, promoting the rapid migration of lithium ions inside the electrode. Nitrogen-doped carbon can introduce defect sites, enhance the electron acceptor capacity of the carbon layer, further improve conductivity, and the carbon layer buffers volume changes, suppresses chemical side reactions, and can also modify the interface wettability through nitrogen atoms, alleviating the problem of high interfacial impedance with solid electrolytes.

[0015] Optionally, when preparing the nitrogen-containing phenolic resin prepolymer, the molar ratio of urea to phenol is 1:(1-1.5), the molar ratio of phenol to formaldehyde is 1:(2.2-2.6), and the mass concentration of the formaldehyde solution is 35-40%.

[0016] Optionally, in step S2, the mass ratio of the coated lithium iron phosphate, porous carbon powder and nitrogen-containing phenolic resin prepolymer is 100:(10-15):(5-8), and the amount of ethanol added is 6-8 times the mass of the coated lithium iron phosphate, and ultrasonic dispersion is performed for 30-60 min. In step S3, the pyrolysis temperature is 600-700℃ and the pyrolysis time is 2-4h.

[0017] Optionally, porous carbon powder is prepared by the following steps: Coffee grounds, melamine, and zinc chloride were mixed in a ratio of 1:(0.6-0.8):(0.3-0.4), ground, and then water was added to obtain a paste-like mixture with a solid content of 40-50%. The mixture was then dried to obtain the precursor. The precursor is heated to 750-800℃ in a nitrogen atmosphere for 2-3 hours, then cooled, crushed, and then soaked in hydrochloric acid solution at a solid-liquid ratio of 1:9-10 for 20-24 hours. After stirring, it is filtered, washed with water until neutral, dried, and ground to obtain porous carbon powder.

[0018] By adopting the above technical solution, zinc chloride, as a Lewis acid, destroys the cellulose and lignin structure in coffee grounds. Moreover, as an activator, it reacts with carbon at high temperature to generate gas, enabling carbon powder etching to form a porous structure. Subsequently, hydrochloric acid soaking dissolves residual zinc oxide and unreacted zinc chloride, while acid washing removes inorganic impurities, exposing more porous structures to obtain nitrogen-doped porous powder. This powder is then used as a raw material to form a conductive network layer, improving electron mobility and further optimizing lithium-ion transport efficiency, thereby enhancing the performance of the cathode material.

[0019] Optionally, the lithium iron phosphate core in step S1 is prepared by the following method: Li2CO3, FeC2O4·2H2O, NH4H2PO4, Mg(NO3)2·6H2O, Al(NO3)3·9H2O and NH4F were mixed and then water and PEG-400 dispersant were added. After ball milling for 2-4 hours, the mixture was spray dried and then calcined at 650-750℃ for 6-8 hours under inert gas to obtain lithium iron phosphate core.

[0020] By adopting the above technical solution, the lithium iron phosphate core in this application is selected from the above-mentioned doped lithium iron phosphate, Mg² + and Al³ + The difference in ionic radius between the ions and iron ions allows the aforementioned cation doping to enter the lithium iron phosphate lattice, introducing lattice defects and enhancing lithium-ion diffusion channels. Furthermore, cation doping also helps to alter the electronic structure, improving the rate performance of the cathode material. - When ions are incorporated into the lithium iron phosphate lattice, they replace some of the O²⁻. -At the position of Mg²⁺, strong fluorine-oxygen bonds are formed. This strong bonding reduces the activity of oxygen on the material surface under high voltage, inhibits oxygen evolution, and thus enhances the stability of the crystal structure. This helps to reduce capacity decay caused by lattice distortion during charge and discharge, and improves cycle stability; moreover, anion doping lowers the migration barrier. Finally, when selecting doped lithium iron phosphate in this application, Mg²⁺ is used to form strong fluorine-oxygen bonds. + / Al³ + Heterobimetallic cation doping (Fe site) and F - Combining anion doping (O site) with cation doping introduces lattice defects to enhance lithium-ion diffusion channels. Anion doping stabilizes the lattice structure and reduces the migration energy barrier, solving the problem of balancing structural stability and ion diffusion rate caused by single doping.

[0021] Optionally, the molar ratio of Li2CO3, FeC2O4·2H2O, NH4H2PO4, Mg(NO3)2·6H2O, Al(NO3)3·9H2O and NH4F is 1:1:1:(0.01-0.02):(0.05-0.1):(0.1-0.15).

[0022] Secondly, this application provides a lithium iron phosphate cathode material, which adopts the following technical solution: A lithium iron phosphate cathode material prepared by the aforementioned method.

[0023] By adopting the above technical solution, the lithium iron phosphate cathode material prepared by the above method has higher lithium-ion transfer efficiency, and improves its cycle stability and rate performance.

[0024] Thirdly, this application provides a semi-solid-state battery, employing the following technical method: A semi-solid-state battery comprising the lithium iron phosphate cathode material.

[0025] In summary, this application has the following beneficial effects: 1. In this application, the lithium iron phosphate core is first coated with an intermediate layer to form a silicate coating layer. The silicate coating layer can prevent lithium iron phosphate from directly contacting the solid electrolyte and suppress interfacial side reactions. At the same time, it can also alleviate the volume change of lithium iron phosphate during charging and discharging, effectively suppress the structural changes of lithium iron phosphate during charging and discharging, and improve the cycle stability of the cathode material. The addition of a mesoporous template agent in the intermediate coating layer guides the formation of a regular mesoporous structure in the hydrothermal reaction. After the template agent is removed by pyrolysis and calcination, a mesoporous structure is formed, which increases the specific surface area of ​​the material, provides more diffusion paths for lithium ions, shortens the transport distance, and the mesoporous structure also reduces the interfacial ion transport resistance. 2. In this application, a conductive network is constructed using porous carbon powder. The high conductivity of the porous carbon powder can compensate for the inherent low electronic conductivity of lithium iron phosphate. Moreover, the pore structure of the porous carbon powder complements the mesopores of the lithium iron phosphate coating layer, forming a three-dimensional conductive network that promotes rapid electron transport within the cathode material. Its pore structure provides additional diffusion paths for lithium ions, solving the problem of ion transport obstruction caused by traditional dense carbon layers. Furthermore, the nitrogen-containing phenolic resin prepolymer carbonizes during pyrolysis, further enhancing the continuity of the conductive network and improving high-rate charge-discharge performance. 3. When using doped lithium iron phosphate in this application, Mg²⁺ is used. + / Al³ + Heterobimetallic cation doping (Fe site) and F - Combining anion doping (O site) with cation doping introduces lattice defects to enhance lithium-ion diffusion channels. Anion doping stabilizes the lattice structure and reduces the migration energy barrier, solving the problem of balancing structural stability and ion diffusion rate caused by single doping. Detailed Implementation

[0026] The present application will be further described in detail below with reference to the embodiments. It should be noted that: unless otherwise specified, the conditions in the following embodiments are carried out according to conventional conditions or the conditions recommended by the manufacturer. Unless otherwise specified, the raw materials used in the following embodiments can be obtained from commercially available sources.

[0027] In the following examples, the PEO-PPO-PEO block copolymer selected is polyethylene oxide-polypropylene oxide-polyethylene oxide (PEO-PPO-PEO) from Angxing New Carbon Materials Changzhou Co., Ltd.

[0028] The following preparation examples illustrate the preparation of nitrogen-containing phenolic resin prepolymers.

[0029] Preparation Example 1

[0030] A method for preparing a nitrogen-containing phenolic resin prepolymer includes the following steps: Phenol was heated to 50°C in an oil bath, and the pH was adjusted to 8.5. A 37% formaldehyde solution and urea were added under stirring, with a molar ratio of urea to phenol of 1:1.2 and a molar ratio of phenol to formaldehyde of 1:2.5. The mixture was heated to 80°C and reacted for 2.5 hours. After cooling, a primary product was obtained. The primary product was diluted with water at a mass ratio of 1:3, and hydrochloric acid was added to adjust the pH to 6.5. The mixture was allowed to stand and separate into layers. The lower layer was then dehydrated under vacuum (-0.09 MPa) at 60°C until the solid content reached 45%, thus obtaining a nitrogen-containing phenolic resin prepolymer.

[0031] Preparation Example 2

[0032] A method for preparing a nitrogen-containing phenolic resin prepolymer includes the following steps: Phenol was heated to 50°C in an oil bath, and the pH was adjusted to 8. A 35% formaldehyde solution and urea were added under stirring, with a molar ratio of urea to phenol of 1:1 and a molar ratio of phenol to formaldehyde of 1:2.2. The mixture was heated to 80°C and reacted for 3 hours. After cooling, a primary product was obtained. The primary product was diluted with water at a mass ratio of 1:3, and hydrochloric acid was added to adjust the pH to 7. The mixture was allowed to stand and separate into layers. The lower layer was then dehydrated under vacuum (vacuum degree -0.09 MPa) at 60°C until the solid content reached 40%, thus obtaining a nitrogen-containing phenolic resin prepolymer.

[0033] Preparation Example 3

[0034] A method for preparing a nitrogen-containing phenolic resin prepolymer includes the following steps: Phenol was heated to 55°C in an oil bath, and the pH was adjusted to 9. A 40% formaldehyde solution and urea were added under stirring, with a molar ratio of urea to phenol of 1:1.5 and a molar ratio of phenol to formaldehyde of 1:2.6. The mixture was heated to 85°C and reacted for 2 hours. After cooling, a primary product was obtained. The primary product was diluted with water at a mass ratio of 1:3, and hydrochloric acid was added to adjust the pH to 7. The mixture was allowed to stand and separate into layers. The lower layer was then dehydrated under vacuum (-0.09 MPa) at 60°C until the solid content reached 50%, thus obtaining a nitrogen-containing phenolic resin prepolymer.

[0035] Comparative Preparation Example 1

[0036] A method for preparing a phenolic resin prepolymer is carried out according to the method in Preparation Example 1, except that urea is not added to the raw materials.

[0037] The following preparation examples are examples of the preparation of lithium iron phosphate cores.

[0038] Preparation Example 4

[0039] A method for preparing a lithium iron phosphate core includes the following steps: Li2CO3, FeC2O4·2H2O, NH4H2PO4, Mg(NO3)2·6H2O, Al(NO3)3·9H2O and NH4F were mixed in a molar ratio of 1:1:1:0.02:0.08:0.12 to obtain a raw material mixture. Then, water and PEG-400 dispersant were added. The amount of water added was 2.5 times the mass of the raw material mixture, and the amount of PEG-400 dispersant added was 2 wt% of the raw material mixture to obtain a slurry. The slurry was then ball-milled for 3 hours and spray-dried. Finally, it was calcined at 700°C for 7 hours under nitrogen as an inert gas to obtain the lithium iron phosphate core.

[0040] Preparation Example 5

[0041] A method for preparing a lithium iron phosphate core includes the following steps: Li2CO3, FeC2O4·2H2O, NH4H2PO4, Mg(NO3)2·6H2O, Al(NO3)3·9H2O and NH4F were mixed in a molar ratio of 1:1:1:0.01:0.05:0.1 to obtain a raw material mixture. Then, water and PEG-400 dispersant were added. The amount of water added was twice the mass of the raw material mixture, and the amount of PEG-400 dispersant added was 1 wt% of the raw material mixture to obtain a slurry. The slurry was then ball-milled for 2 hours and spray-dried. Finally, it was calcined at 650°C for 8 hours under nitrogen as an inert gas to obtain the lithium iron phosphate core.

[0042] Preparation Example 6

[0043] A method for preparing a lithium iron phosphate core includes the following steps: Li2CO3, FeC2O4·2H2O, NH4H2PO4, Mg(NO3)2·6H2O, Al(NO3)3·9H2O and NH4F were mixed in a molar ratio of 1:1:1:0.02:0.1:0.15 to obtain a raw material mixture. Then, water and PEG-400 dispersant were added. The amount of water added was 3 times the mass of the raw material mixture, and the amount of PEG-400 dispersant added was 3 wt% of the raw material mixture to obtain a slurry. The slurry was then ball-milled for 4 hours and spray-dried. Finally, it was calcined at 750°C for 6 hours under nitrogen as an inert gas to obtain the lithium iron phosphate core.

[0044] Preparation Example 7

[0045] A method for preparing lithium iron phosphate cores is carried out according to the method in Preparation Example 4, except that Mg(NO3)2·6H2O, Al(NO3)3·9H2O and NH4F are not added to the raw materials.

[0046] Preparation Example 8

[0047] A method for preparing lithium iron phosphate cores is carried out according to the method in Preparation Example 4, except that NH4F is not added to the raw materials.

[0048] Preparation Example 9

[0049] A method for preparing lithium iron phosphate cores is carried out according to the method in Preparation Example 4, except that Mg(NO3)2·6H2O is not added to the raw materials.

[0050] Preparation Example 10

[0051] A method for preparing lithium iron phosphate cores is carried out according to the method in Preparation Example 4, except that Mg(NO3)2·6H2O and Al(NO3)3·9H2O are not added to the raw materials.

[0052] Example 1

[0053] A method for preparing a lithium iron phosphate cathode material includes the following steps: S1. LiNO3, (NH4)3PO4 and Na2SiO3 are mixed in a Li:P:Si molar ratio of 1:0.9:0.08, and then added to water to prepare a mixed aqueous solution. The concentration of LiNO3 in the mixed aqueous solution is 0.3 mol / L. Then, the lithium iron phosphate core prepared in Preparation Example 4 is dispersed in the mixed aqueous solution containing LiNO3, (NH4)3PO4 and Na2SiO3. The mass ratio of lithium iron phosphate core to mixed aqueous solution is 1:4.5. Then, the pH value was adjusted to 9.5, and a hydrothermal reaction was carried out at 70℃. At the same time, a mesoporous template agent was added, with the amount of mesoporous template agent added being 5wt% of the mass of the lithium iron phosphate core. The reaction was carried out for 5 hours. After the reaction was completed, the core was centrifuged, washed, and dried. Then, the core was calcined under nitrogen as an inert atmosphere to remove the mesoporous template agent. The calcination temperature was 400℃ and the calcination time was 2.5 hours to obtain coated lithium iron phosphate. Among them, the mesoporous template agent is a PEO-PPO-PEO block copolymer; S2. The coated lithium iron phosphate, porous carbon powder and nitrogen-containing phenolic resin prepolymer prepared in step S1 are mixed at an addition ratio of 100:12:6. Then ethanol is added, and the amount of ethanol added is 6-8 times the mass of the coated lithium iron phosphate. After ultrasonic dispersion at a power of 80W for 40 minutes, a suspension is formed. Then spray drying is performed to obtain composite precursor particles. S3. The composite precursor particles were pyrolyzed in a nitrogen atmosphere to obtain lithium iron phosphate cathode material. The pyrolysis temperature was 650℃ and the pyrolysis time was 3h.

[0054] In step S3, the porous carbon powder used is ordered porous carbon powder NCP from Angxing New Carbon Materials Changzhou Co., Ltd., specifically high-porosity ordered porous carbon powder NCP-HV.

[0055] Example 2

[0056] A method for preparing a lithium iron phosphate cathode material includes the following steps: S1. LiNO3, (NH4)3PO4 and Na2SiO3 are mixed in a Li:P:Si molar ratio of 1:0.8:0.05, and then added to water to prepare a mixed aqueous solution. The concentration of LiNO3 in the mixed aqueous solution is 0.1 mol / L. Then, the lithium iron phosphate core prepared in Preparation Example 5 is dispersed in the mixed aqueous solution containing LiNO3, (NH4)3PO4 and Na2SiO3, and the mass ratio of lithium iron phosphate core to mixed aqueous solution is 1:4. Then, the pH value was adjusted to 9, and a hydrothermal reaction was carried out at 60℃. At the same time, a mesoporous template agent was added, with the amount of mesoporous template agent added being 3wt% of the mass of the lithium iron phosphate core. The reaction was carried out for 4 hours. After the reaction was completed, the core was centrifuged, washed, and dried. Then, the core was calcined in a nitrogen inert atmosphere to remove the mesoporous template agent. The calcination temperature was 350℃ and the calcination time was 3 hours to obtain coated lithium iron phosphate. Among them, the mesoporous template agent is a PEO-PPO-PEO block copolymer; S2. The coated lithium iron phosphate, porous carbon powder and nitrogen-containing phenolic resin prepolymer prepared in step S1 are mixed at an addition ratio of 100:10:5. Then ethanol is added, and the amount of ethanol added is 6 times the mass of the coated lithium iron phosphate. After ultrasonic dispersion at a power of 80W for 30 minutes, a suspension is formed. Then spray drying is performed to obtain composite precursor particles. S3. The composite precursor particles were pyrolyzed in a nitrogen atmosphere to obtain lithium iron phosphate cathode material. The pyrolysis temperature was 600℃ and the pyrolysis time was 4h.

[0057] In step S3, the porous carbon powder used is ordered porous carbon powder NCP from Angxing New Carbon Materials Changzhou Co., Ltd., specifically high-porosity ordered porous carbon powder NCP-HV.

[0058] Example 3

[0059] A method for preparing a lithium iron phosphate cathode material includes the following steps: S1. LiNO3, (NH4)3PO4 and Na2SiO3 are mixed in a Li:P:Si molar ratio of 1:1:0.1, and then added to water to prepare a mixed aqueous solution. The concentration of LiNO3 in the mixed aqueous solution is 0.5 mol / L. Then, the lithium iron phosphate core prepared in Preparation Example 6 is dispersed in the mixed aqueous solution containing LiNO3, (NH4)3PO4 and Na2SiO3, and the mass ratio of lithium iron phosphate core to mixed aqueous solution is 1:5. Then, the pH value was adjusted to 10, and a hydrothermal reaction was carried out at 80℃. At the same time, a mesoporous template agent was added, with the amount of mesoporous template agent added being 6wt% of the mass of the lithium iron phosphate core. The reaction was carried out for 6 hours. After the reaction was completed, the core was centrifuged, washed, and dried. Then, the core was calcined in a nitrogen inert atmosphere to remove the mesoporous template agent. The calcination temperature was 450℃ and the calcination time was 2 hours to obtain coated lithium iron phosphate. Among them, the mesoporous template agent is a PEO-PPO-PEO block copolymer; S2. The coated lithium iron phosphate, porous carbon powder and nitrogen-containing phenolic resin prepolymer prepared in step S1 are mixed at an addition ratio of 100:15:8. Then ethanol is added, and the amount of ethanol added is 8 times the mass of the coated lithium iron phosphate. After ultrasonic dispersion at a power of 80W for 60 minutes, a suspension is formed. Then spray drying is performed to obtain composite precursor particles. S3. The composite precursor particles were pyrolyzed in a nitrogen atmosphere to obtain lithium iron phosphate cathode material. The pyrolysis temperature was 700℃ and the pyrolysis time was 2h.

[0060] In step S3, the porous carbon powder used is ordered porous carbon powder NCP from Angxing New Carbon Materials Changzhou Co., Ltd., specifically high-porosity ordered porous carbon powder NCP-HV.

[0061] Preparation Examples 4-7

[0062] A method for preparing a lithium iron phosphate cathode material is carried out according to the method in Preparation Example 1, except that the lithium iron phosphate core in step S1 is selected from the lithium iron phosphate cores prepared in Preparation Examples 7-10.

[0063] Example 8

[0064] A method for preparing a lithium iron phosphate cathode material is carried out according to the method in Preparation Example 1, except that the porous carbon powder in step S2 is obtained by the following method: Coffee grounds, melamine, and zinc chloride were mixed in a ratio of 1:0.7:0.3 and then ground. Water was added to obtain a paste-like mixture with a solid content of 45%, which was then dried to obtain the precursor. The precursor was heated to 780℃ for 2.5 h under a nitrogen atmosphere, then cooled and pulverized. It was then soaked in 1 mol / L hydrochloric acid solution at a solid-liquid ratio of 1:10 for 22 h, stirred and filtered, washed with water until neutral, dried under vacuum at 80℃, and then ground through a 300-mesh sieve to obtain porous carbon powder.

[0065] Example 9

[0066] A method for preparing a lithium iron phosphate cathode material is carried out according to the method in Preparation Example 1, except that the porous carbon powder in step S2 is obtained by the following method: Coffee grounds, melamine, and zinc chloride were mixed in a ratio of 1:0.6:0.3 and then ground. Water was added to obtain a paste-like mixture with a solid content of 40%, which was then dried to obtain the precursor. The precursor was heated to 750℃ for 3 hours under a nitrogen atmosphere, then cooled and pulverized. It was then soaked in a 1 mol / L hydrochloric acid solution at a solid-liquid ratio of 1:9 for 20 hours, stirred and filtered, washed with water until neutral, vacuum dried at 80℃, and then ground through a 300-mesh sieve to obtain porous carbon powder.

[0067] Example 10

[0068] A method for preparing a lithium iron phosphate cathode material is carried out according to the method in Preparation Example 1, except that the porous carbon powder in step S2 is obtained by the following method: Coffee grounds, melamine, and zinc chloride were mixed in a ratio of 1:0.8:0.4 and then ground. Water was added to obtain a paste-like mixture with a solid content of 50%, which was then dried to obtain the precursor. The precursor was heated to 800℃ for 2 hours under a nitrogen atmosphere, then cooled and pulverized. It was then soaked in a 1 mol / L hydrochloric acid solution at a solid-liquid ratio of 1:10 for 24 hours, stirred and filtered, washed with water until neutral, vacuum dried at 80℃, and then ground through a 300-mesh sieve to obtain porous carbon powder.

[0069] Comparative Example 1

[0070] A method for preparing a lithium iron phosphate cathode material is carried out according to the method in Example 1, except that the nitrogen-containing phenolic resin prepolymer in step S2 is replaced by an equal amount of the phenolic resin prepolymer obtained in Comparative Preparation Example 1.

[0071] Comparative Example 2

[0072] A method for preparing a lithium iron phosphate cathode material is carried out according to the method in Example 1, except that step S1 is not performed, and the lithium iron phosphate core is directly mixed with porous carbon powder and nitrogen-containing phenolic resin prepolymer in step S2.

[0073] Comparative Example 3

[0074] A method for preparing a lithium iron phosphate cathode material is carried out according to the method in Example 1, except that porous carbon powder is not added in step S2.

[0075] Comparative Example 4

[0076] A method for preparing a lithium iron phosphate cathode material is carried out according to the method in Example 1, except that no mesoporous template agent is added in step S1.

[0077] Performance testing

[0078] First, the lithium iron phosphate cathode material was tested for lithium-ion diffusion coefficient by constant current intermittent titration (GITT), and the test results are shown in Table 1.

[0079] Table 1:

[0080] Based on the test results in Table 1 above, the lithium iron phosphate cathode material prepared in this application embodiment has a good lithium-ion diffusion coefficient, which is more conducive to improving the cycle performance and rate performance of the subsequent battery; combined with the test results in Example 1 and Examples 4-7, it can be seen that the lithium iron phosphate in Example 1 is improved by doping with Mg²⁺ + and Al³ + (Fe site) and F - When the (O-site) combination forms a double-doped structure, the lithium-ion diffusion coefficient is significantly improved, while in Example 4, the undoped lithium-ion diffusion coefficient is significantly reduced, combined with the undoped F in Example 5. - When compared to Example 1, its lithium-ion diffusion coefficient is lower. When combining Examples 9 and 10, only Mg²⁺ is doped. + Or only doped with Mg² + and Al³ + At that time, its lithium-ion diffusion coefficient was still lower than that of Example 1, Mg² + / Al³ + (Fe site) and F - Co-doping at (O sites) and the introduction of lattice defects help improve the lithium-ion diffusion coefficient.

[0081] Combining the test results of Examples 8-10, when nitrogen-doped porous carbon powder is prepared using a specific method, nitrogen doping alters the electronic structure of the carbon material, improves electron acceptor capacity, enhances electron mobility, and constructs lithium-ion transport bridges. Combined with the mesoporous structure of the intermediate coating layer, this further improves lithium-ion transport efficiency. Furthermore, considering the test results of Comparative Example 1, where a common phenolic resin prepolymer was used instead of a nitrogen-containing phenolic resin prepolymer, the lithium-ion diffusion coefficient was significantly reduced. Nitrogen doping in the phenolic resin prepolymer plays a crucial role in lithium-ion transport efficiency and conductivity. It plays an important role. Combining the detection results in Comparative Example 2, in Comparative Example 2, the lithium iron phosphate was not coated with the intermediate layer in step S1, and the carbon powder coating in step S2 was directly performed. It can be seen that its lithium ion diffusion coefficient was also reduced. Combining the detection results in Comparative Example 3 and Comparative Example 4, when no porous carbon powder or mesoporous template agent was added, its lithium ion diffusion coefficient was significantly reduced. Porous carbon powder utilizes the conductive network effect of carbon powder and mesoporous structure to help improve its conductivity and ion diffusion coefficient, while the addition of mesoporous template agent forms a mesoporous structure, which helps ion conduction.

[0082] Furthermore, the lithium iron phosphate cathode material from the above embodiments and comparative examples was applied to the preparation of semi-solid-state batteries. Specifically, PVDF binder and N-methylpyrrolidone solvent were mixed in a ratio of 1:9, and then the lithium iron phosphate cathode material obtained in the above embodiments and comparative examples was added to prepare a slurry with a solid content of 70%. This slurry was coated onto an aluminum foil current collector, dried, and rolled to obtain a cathode sheet. The cathode sheet was then applied to the preparation of semi-solid-state batteries. The negative electrode of the semi-solid-state battery was graphite, and the electrolyte was a polymer-based semi-solid electrolyte injected under vacuum. The battery was assembled using a stacking process and a ceramic-coated polyolefin separator. The polymer-based semi-solid electrolyte was made of 55 wt% polymer matrix, 15 wt% lithium salt, and 30 wt% plasticizer. The polymer matrix was polyvinylidene fluoride, and the plasticizer was ethylene carbonate.

[0083] The obtained batteries were then tested for rate performance and cycle performance. Specifically, the capacity retention rate was tested by performing 100 cycles at 1C under a voltage of 2.0-3.65V. In addition, the batteries were charged at 2C and 5C rates to the upper limit voltage of 3.65V, and then discharged at the same rate to the lower limit voltage of 2.0V after resting. The 2C capacity retention rate and 5C capacity retention rate were measured. The results are shown in Table 2 below.

[0084] Table 2:

[0085] Based on the test results in Table 2 above, the lithium iron phosphate cathode material prepared by the synergistic effect of the lithium iron phosphate core, porous coating layer, and subsequent porous carbon powder in Examples 1-3 of this application exhibits excellent cycle stability and high-rate ion transport efficiency. Based on the test results of Examples 8-10, the addition of nitrogen-doped carbon powder can further optimize the ion transport path and improve battery performance. Based on the test results of Examples 4-7, the doping elements of lithium iron phosphate also have a significant impact on its performance. Furthermore, based on the test results of Comparative Example 1, when ordinary phenolic resin was used in Comparative Example 1, both its cycle performance and rate performance were reduced. The nitrogen-containing carbon layer plays an important role in interface stability and lithium-ion transport. Based on the test results of Comparative Example 2, its performance was also reduced when no intermediate layer coating was applied. Based on the test results of Comparative Examples 3 and 4, lithium-ion transport was reduced when the coating layer or outer layer did not form a mesoporous structure.

[0086] This specific embodiment is merely an explanation of this application and is not intended to limit it. After reading this specification, those skilled in the art can make modifications to this embodiment without contributing any inventive step, but such modifications are protected by patent law as long as they fall within the scope of the claims of this application.

Claims

1. A method for preparing a lithium iron phosphate cathode material, characterized in that, Includes the following steps: S1. The lithium iron phosphate core is dispersed in a mixed aqueous solution containing LiNO3, (NH4)3PO4 and Na2SiO3, and a hydrothermal reaction is carried out under alkaline conditions. At the same time, a mesoporous template agent is added. After the reaction is completed, the core is centrifuged, washed, dried, and then calcined under an inert atmosphere to remove the mesoporous template agent, thus obtaining coated lithium iron phosphate. S2. The prepolymer of coated lithium iron phosphate, porous carbon powder and nitrogen-containing phenolic resin obtained in step S1 is mixed with ethanol, ultrasonically dispersed to form a suspension, and then spray-dried to obtain composite precursor particles. S3. Lithium iron phosphate cathode material is prepared by pyrolyzing composite precursor particles in a nitrogen atmosphere. The nitrogen-containing phenolic resin prepolymer in step S2 is obtained through the following steps: Phenol was heated to 50-55℃ in an oil bath, and the pH was adjusted to 8-9. Formaldehyde solution and urea were added under stirring, and the temperature was raised to 80-85℃. The reaction was maintained at this temperature for 2-3 hours. After cooling, water was added to dilute the solution and the pH was adjusted to 6-7. The mixture was allowed to stand and separate into layers. The lower layer was taken and dehydrated until the solid content was 40-50% to obtain a nitrogen-containing phenolic resin prepolymer. The lithium iron phosphate core in step S1 is prepared by the following method: Li2CO3, FeC2O4·2H2O, NH4H2PO4, Mg(NO3)2·6H2O, Al(NO3)3·9H2O and NH4F were mixed and then water and PEG-400 dispersant were added. After ball milling for 2-4 hours, the mixture was spray dried and then calcined at 650-750℃ for 6-8 hours under inert gas to obtain lithium iron phosphate core. The molar ratio of Li2CO3, FeC2O4·2H2O, NH4H2PO4, Mg(NO3)2·6H2O, Al(NO3)3·9H2O and NH4F is 1:1:1:(0.01-0.02):(0.05-0.1):(0.1-0.15).

2. The method for preparing a lithium iron phosphate cathode material according to claim 1, characterized in that: The mesoporous template agent in step S1 is selected from polymethyl methacrylate microspheres or PEO-PPO-PEO block copolymers.

3. The method for preparing a lithium iron phosphate cathode material according to claim 1, characterized in that: In step S1, LiNO3, (NH4)3PO4 and Na2SiO3 are added in a molar ratio of Li:P:Si of 1:(0.8-1):(0.05-0.1), and the concentration of LiNO3 in the mixed aqueous solution is 0.1-0.5 mol / L, and the mass ratio of lithium iron phosphate core to mixed aqueous solution is 1:(4-5). The alkaline conditions are pH 9-10, and the hydrothermal reaction is carried out at 60-80℃. The amount of mesoporous template agent added is 3-6 wt% of the mass of lithium iron phosphate core. The calcination temperature is 350-450℃, and the calcination time is 2-3 hours.

4. The method for preparing a lithium iron phosphate cathode material according to claim 1, characterized in that: When preparing nitrogen-containing phenolic resin prepolymer, the molar ratio of urea to phenol is 1:(1-1.5), the molar ratio of phenol to formaldehyde is 1:(2.2-2.6), and the mass concentration of formaldehyde solution is 35-40%.

5. The method for preparing a lithium iron phosphate cathode material according to claim 1, characterized in that: In step S2, the mass ratio of the coated lithium iron phosphate, porous carbon powder and nitrogen-containing phenolic resin prepolymer is 100:(10-15):(5-8), and the amount of ethanol added is 6-8 times the mass of the coated lithium iron phosphate. The mixture is ultrasonically dispersed for 30-60 min. In step S3, the pyrolysis temperature is 600-700℃ and the pyrolysis time is 2-4h.

6. The method for preparing a lithium iron phosphate cathode material according to claim 1, characterized in that: Porous carbon powder is prepared through the following steps: Coffee grounds, melamine, and zinc chloride were mixed in a ratio of 1:(0.6-0.8):(0.3-0.4), ground, and then water was added to obtain a paste-like mixture with a solid content of 40-50%. The mixture was then dried to obtain the precursor. The precursor is heated to 750-800℃ in a nitrogen atmosphere for 2-3 hours, then cooled, crushed, and then soaked in hydrochloric acid solution at a solid-liquid ratio of 1:9-10 for 20-24 hours. After stirring, it is filtered, washed with water until neutral, dried, and ground to obtain porous carbon powder.

7. A lithium iron phosphate cathode material prepared by the preparation method according to any one of claims 1-6.

8. A semi-solid-state battery, characterized in that: Including the lithium iron phosphate cathode material as described in claim 7.

Citation Information

Patent Citations

  • Multicomponent doping spherical lithium iron phosphate anode material and method of manufacturing the same

    CN101369657A

  • Conductive and ionic double-layer in-situ coated lithium iron phosphate as well as preparation method and application thereof

    CN114335481A

  • Method for preparing lithium iron phosphate from nitrogen-doped phenolic resin by liquid phase method

    CN118458725A

  • Preparation method and application of nitrogen-doped biomass carbon lithium ion battery negative electrode material based on coffee grounds

    CN120736523A

  • Positive electrode active material and electrolyte composition for lithium ion battery

    CN121748531A